Economic Bubble and Fraud in Unicorn Startups: A Case Study of eFishery - Akbar Firmansyah; Akas Setiawan; Waridad Al Ayyubi (Penerbit Jurnal Indonesia, 2026)
Examine the lifecycle of the Indonesian startup eFishery using the Minsky and Kindleberger economic bubble framework. A qualitative single-case study design was employed, based on extensive secondary data analysis of investigative media reports, forensic audit summaries, and industry publications. Findings demonstrate a clear alignment between eFishery’s development and the five stages of an economic bubble: displacement, boom, euphoria, financial distress, and revulsion. Internal financial dynamics were mapped to Minsky’s regimes of hedge, speculative, and Ponzi finance, revealing how staged venture capital funding created structural incentives that contributed to financial manipulation. Governance failures were identified as principal drivers, notably moral hazard between founders and investors and a pervasive growth-at-all-costs culture, which accelerated both the bubble’s expansion and its subsequent collapse. The Minsky and Kindleberger framework was found to be an effective analytical tool for assessing firm-level financial instability in high-growth startups. Implications are discussed for regulators, investors, and founders, with recommendations for improved governance, transparency, and funding practices to mitigate systemic risks associated with the pursuit of unicorn valuations.